Ten Changes Psychotherapists Typically Make as They Mature Into the Role of Supervisor. Issue 11 (17th September 2014) - Goodyear, Rodney; Lichtenberg, James W.; Bang, Keeyeon; Gragg, Janee Both
<x xml:space="preserve">Abstract</x> Stage models have largely informed scholarship on supervisor developmental processes. We argue that understanding this development as occurring along dimensions is more useful for both supervision practitioners and educators as well as for those engaged in research on supervisor development. Building on the work of Heid (1997) and working with a panel of 7 supervision experts, we identify 10 themes and validate their salience to supervisor development using a sample of 22 clinical supervisors. We describe and elaborate on each theme, and then present and discuss a case vignette that illustrates many of the supervisor developmental themes.